Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1109/10.46257
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac energy considerations during intraaortic balloon pumping

Abstract: Cardiac oxygen availability and oxygen consumption were used in a theoretical study as indexes of myocardial energy supply and utilization, respectively. A detailed computer simulation of the closed-loop canine cardiovascular system was utilized to study the dependence of these indexes on timing of the intraaortic balloon pump. Oxygen availability exhibited higher sensitivity to balloon timing than oxygen utilization. While maximum augmentation of oxygen availability was 58 percent, oxygen consumption could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Schreuder et al 4 confirmed the findings of Cheung et al, 9 showing that an IABP reduced left ventricular end-systolic pressure and volume, improved stroke volume, reduced left ventricular stroke work (LVSW), and reduced left ventricular end-diastolic pressure and volume. In contrast to Barnea et al, 5 Schreuder et al 4 and Cheung et al 9 concluded that afterload reduction was the primary mechanism by which an IABP improved left ventricular performance immediately (within 20 seconds), because improvement in coronary flow cannot occur within that time, and that therefore an IABP is critically important in heart failure patients without ischemia. I ntra-aortic balloon counterpulsation (IABC) is the most widely used form of left ventricular mechanical support today; more than 160 000 patients worldwide receive this therapy annually.…”
Section: Physiological Effects Of Iabcmentioning
confidence: 67%
See 4 more Smart Citations
“…Schreuder et al 4 confirmed the findings of Cheung et al, 9 showing that an IABP reduced left ventricular end-systolic pressure and volume, improved stroke volume, reduced left ventricular stroke work (LVSW), and reduced left ventricular end-diastolic pressure and volume. In contrast to Barnea et al, 5 Schreuder et al 4 and Cheung et al 9 concluded that afterload reduction was the primary mechanism by which an IABP improved left ventricular performance immediately (within 20 seconds), because improvement in coronary flow cannot occur within that time, and that therefore an IABP is critically important in heart failure patients without ischemia. I ntra-aortic balloon counterpulsation (IABC) is the most widely used form of left ventricular mechanical support today; more than 160 000 patients worldwide receive this therapy annually.…”
Section: Physiological Effects Of Iabcmentioning
confidence: 67%
“…Schreuder et al 4 were the first to show the effect of timing on left ventricular dyssynchrony and concluded that early inflation is the worst timing error, reducing both left ventricular performance and IABP efficacy. Although late inflation has not been studied, several investigators 3,5,6 have concluded that late inflation reduces augmentation time and coronary artery perfusion pressure.…”
Section: Conventional Timingmentioning
confidence: 99%
See 3 more Smart Citations